Identifikasi Karakteristik Bio-Fisik Habitat Peneluran Penyu di Pulau Bunaken – Taman Nasional Bunaken - Kezia Melania Clara Tiwa; Sendy Beatrix Rondonuwu; Hanry Jefry Lengkong; Eko Wahyu Handoyo (Jurnal MIPA, 2023)
Bunaken Island is one of the islands in Manado City, North Sulawesi Province which is one of the turtle nesting areas and has been designated as a Bunaken National Park Conservation Area. Turtles are protected animals based on Government Regulation No. 7 of 1999 concerning the preservation of plant and animal species and Government Regulation No. 8 of 1999 concerning the use of wild plant and animal species. Beach characteristics are an option for turtles in determining nesting locations. Research on the bio-physical characteristics of turtle nesting habitats on Bunaken Island for conservation efforts so that the conditions of turtle nesting habitats are maintained. The method used in this research is descriptive exploratory method. With bio-physical parameters consisting of measurements of beach width, temperature, humidity, sand texture, beach slope, coastal vegetation and the presence of predators. The results showed that stations 1 and 3 correspond to turtle nesting habitats with an evaluation value obtained of 100%. As for station 2 with an evaluation value of 73.33%, which means it is quite appropriate and the station has a limit that can be tolerated.Â